Discovery of boronic acid-based fluorescent probes targeting amyloid-beta plaques in Alzheimer's disease. Issue 7 (1st April 2016) - Jung, Seung-Jin; Lee, Jun Young; Kim, Tae Ho; Lee, Dong-Eun; Jeon, Jongho; Yang, Seung Dae; Hur, Min Goo; Min, Jung-Joon; Park, Yong Dae
Graphical abstract: Abstract: A boronic acid-based fluorescent probe was developed for diagnosis of amyloid-β (Aβ) plaques from Alzheimer's disease (AD). Probe4c, which included boronic acid as a functional group, exhibited a significant increase (64.37-fold, F Aβ / F 0 ) in fluorescence intensity as a response to Aβ aggregates, with a blue shift (105 nm) in the maximum emission wavelength. We found that boronic acid as a functional group improved the binding affinity ( K D value = 0.79 ± 0.05 μM for4c ) for Aβ aggregates and confirmed that4c selectively stained Aβ plaques in brain sections from APP/PS1 mice. Ex vivo fluorescence imaging using mice (normal and APP/PS1) also revealed that4c was able to penetrate the blood–brain barrier (BBB) and to stain Aβ plaques in the brain. From these results, we believe that4c will be useful as a fluorescent probe in preclinical research related to AD. Furthermore, we believe that our results with boronic acid also provide valuable information for the development of a probe for Aβ plaques.